Warpage measurements to support the development of mmWave modules. (November 2022) - Albrecht, Oliver; Meier, Karsten; Schaulin, Michael; Toussaint, Pierre-Louis; Gamba, Baptiste; Cruz, Rodolfo; Vernhes, Pierre; Götze, Christian; Bock, Karlheinz
Abstract: Consumer electronics and the automotive sector are increasingly becoming important as fields of application for mmWave, radio frequency and radar technology. As artificial intelligence, human-machine-interaction, and advanced driver assistance systems (ADAS) are reaching to the next level, innovative approaches and materials for electronics packaging are needed. The development of novel packages and modules for high frequency applications and harsh environment requires a detailed quality and reliability assessment. However, it is necessary to build up an in-depth understanding of the mechanical properties of the materials used and to analyze their thermomechanical behavior as a composite. E.g., different Young's moduli and coefficients of thermal expansion can cause deformation and warpage. This can result into failures of solder joints under thermal load conditions. In this study, a warpage investigation of an mmWave test module from a tension free state up to a mounted state at board level is performed.